Pemanfaatan Black Garlic Dalam Pembuatan Saus Hoisin: - Atmojo, Heri; Batrisyia Arifin, Adelina (JURNAL PARIWISATA VOKASI, 2024)
The study aims to determine the difference in taste of experimental black garlic hoisin sauce with comparison sauce, determine the nutritional content of black garlic hoisin sauce with comparison sauce and determine the cost of making black garlic hoisin sauce with comparison sauce. The research method used is experimental research. By collecting data through questionnaires to professional and non-professional panelist respondents through organoleptic tests. Data analysis techniques in the form of documents, notes, and recordings. Conclusions and suggestions 1. Taste of Black Gar-lic Hoisin Sauce and Black Garlic Hoisin Sauce Comparison, a/b. aspects of the aroma & taste of experimental hoisin sauce are preferred and the most delicious, c. aspects of the texture of experimental hoisin sauce and original hoisin sauce are both thick. d. appearance aspects, experimental hoisin sauce is more attractive. 2. Caloric Nutritional Value of Hoisin Sauce Black Garlic Hoisin Sauce The comparison is greater in nutritional composition than the experiment. 3. The food cost of the experimental Black Garlic Hoisin Sauce is relatively lower.